Back to the roots? Dual cannulation strategy for ambulatory ECMO in adolescent lung transplant candidates: An alternative?. (1st March 2017) - Schmidt, F.; Jack, T.; Sasse, M.; Mueller, C.; Schwerk, N.; Bobylev, D.; Beerbaum, P.; Koeditz, H.
Abstract: Bridging critically ill pediatric patients to lung transplantation still remains a major challenge. Although still controversial, within the last 5 years, ECMO has been increasingly used as a bridge to lung transplantation concept in adult and pediatric patients with acceptable outcomes. The outstanding developments in the field of extracorporeal devices and the introduction of awake ECMO concepts with the avoidance of mechanical ventilation have led to a real paradigm shift in the ICU management of pretransplant candidates with severe respiratory failure. Therefore, ECMO is no longer seen as a contraindication for lung transplantation at least at our center. Nevertheless, how to bridge these patients on ECMO still remains controversial. Thus, we introduced an ambulatory ECMO approach in adolescent lung transplant candidates with acute respiratory failure using a dual cannulation strategy and hereby present first results from this procedure.